The informational and methodical support of the aerospace monitoring of a sea shelf for the detection of anomalies over hydrocarbon deposits - Fedorovsky, O.D.; Khyzhniak, A.V.; Sedlerova, O.V.; Tovstyuk, Z.M.; Efimenko, T.A.; Porushkevich, A.Yu. (Доповіді НАН України, 2019)
The article describes the informational and methodological support of the aerospace monitoring of a sea shelf for
revealing the temperature and optical anomalies over the deposits of hydrocarbons. The geology-geophysical and
hydrophysical factors, as the most important ones, affecting the efficiency of the searching for hydrocarbon deposits
are considered. It is established that, between the hydrophysical and hydrodynamic processes in near-surface water
layers on the boundary between water and atmosphere, dynamical processes in a fluid, geological structure of the
lithosphere, and underwater landscapes, there is an interconnection that should be taken into account, when detecting
the hydrocarbon deposit, by using the remote sensing. Виконано аналіз інформаційно-методичного забезпечення аерокосмічного моніторингу морського шельфу для виявлення температурних і оптичних аномалій над покладами вуглеводнів. Розглянуто геолого-геофізичний і гідролого-гідрофізичний фактори, як найважливіші, що впливають на ефективність пошуку
покладів вуглеводнів. Встановлено, що між гідрофізичними, гідродинамічними процесами в приповерхневих шарах води на межі розділу вода—атмосфера, флюїдодинамічними процесами і геологічною будовою
літосфери та підводних ландшафтів існує взаємозв’язок, який необхідно враховувати при виявленні покладів вуглеводнів на основі дистанційної космічної зйомки. Выполнен анализ информационно-методического обеспечения аэрокосмического мониторинга морского
шельфа для выявления температурных и оптических аномалий над залежами углеводородов. Рассмотрены
геолого-геофизический и гидролого-гидрофизический факторы, как важнейшие, влияющие на эффективность поиска залежей углеводородов. Установлено, что между гидрофизическими, гидродинамическими
процессами в приповерхностных слоях воды на границе раздела вода—атмосфера, флюидодинамическими процессами, геологическим строением литосферы и подводных ландшафтов существует взаимосвязь,
которую необходимо учитывать при выявлении залежей углеводородов на основе дистанционной космической съемки.